Analysis of diastolic left ventricular wall shear stress in normal people of different age groups - Dong, Liping; Li, Hairu; Xu, Xiangli; Ren, Min; Yu, Weidong; Bai, Wenkun; Sun, Di; Tian, Jiawei (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Diastolic wall shear stress (WSS), assessed by using vector flow mapping (VFM), is the result of the interaction between the blood flow and the ventricular wall. This study aimed to evaluate the trend of left ventricular (LV) WSS in normal subjects. Methods and Results: A total of 371 healthy volunteers were recruited and divided into four age groups (group I: 18–30 years; group II: 31–43 years; group III: 44–56 years; group IV: 57–70 years). LV WSS of different age groups was measured at each diastolic phase ( P1: isovolumic diastolic period, P2: rapid filling period, P3: slow filling period, and P4:atrial contraction period ) to evaluate the change trend of LV WSS. In each age group, LV WSS coincided with a trend of increasing-decreasing-increasing during P1–P4 (P < 0.05). Besides, among groups I, II, III, and IV, WSS of anterolateral, inferoseptal, and anteroseptal in P1 and WSS of inferolateral, inferoseptal, and anteroseptal in P4 all showed an increasing trend with age (P < 0.05). Regarding sex differences, women had greater diastolic WSS compared to men (P < 0.05). Conclusions: LV WSS showed a regular variation and had specific age- and sex-related patterns in different diastolic phases.